Workshop Pengolahan Kedelai menjadi Soyghurt pada Program Kemitraan Masyarakat (PKM) Bioteknologi Soyghurt MGMP IPA Kabupaten Maros - Nurhayani H. Muhiddin; Sitti Rahma Yunus; Sitti Saenab; Muh. Tawil (JKM: Jurnal Kemitraan Masyarakat, 2023)
This Community Partnership Program implementation activity was carried out with the aim of providing education to the community, especially science teachers within the scope of the Maros Regency Science MGMP. This activity specifically aims to increase the knowledge and skills of science teachers in developing biotechnology for processing soybeans into fermented soy milk (Soyghurt). Evaluation of knowledge through filling out questionnaires. The results of the evaluation of service activities show that the average participant response to the process of making Soyghurt from the training material aspect is in the strongly agree (58%) and agree (42%) categories, while the training method aspect is in the strongly agree (68%) category. and the agree category (32%). Thus, it was concluded that overall, the training materials and methods of implementing service were considered useful and very effective in achieving training objectives, as well as providing positive learning experiences to participants.